2011
DOI: 10.4314/tjpr.v9i6.63555
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Expiry of Essential Medicines and Supplies During the ‘Pull’ and ‘Push’ Drug Acquisition Systems in a Rural Ugandan Hospital

Abstract: Purpose: To assess the impact of the 'Pull' system on the availability and reduction of expiry of essential medicines and medical supplies and to determine factors affecting their availability in Kilembe Hospital, Uganda. Methods: Records of 27 essential medicines and 11 medical supplies were reviewed over two-year periods in the Push (2000Push ( -2001 and Pull system (2004Pull system ( -2005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 3 publications
2
27
2
1
Order By: Relevance
“…The difference could possibly be attributed to the differences in the etiological differences in the locations from which theses studies were conducted. In this study ACT Artemether/ lumefantrine (20/120 mg) had the highest percentage stock-out followed by Cotrimoxazole 480mg, unlike what was noted by another study [8], which noted Quinine tablets had the highest percentage stock-out in the push system followed by ciprofloxacin and while diclofenac injection had the highest percentage stockout in the pull system followed by ferrous sulphate tablets. Since ACT Artemether/ lumefantrine (20/120 mg) tablets are used in the treatment of malaria, the stock-outs of this drug could have had a severe impact on the health of the population within the district.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The difference could possibly be attributed to the differences in the etiological differences in the locations from which theses studies were conducted. In this study ACT Artemether/ lumefantrine (20/120 mg) had the highest percentage stock-out followed by Cotrimoxazole 480mg, unlike what was noted by another study [8], which noted Quinine tablets had the highest percentage stock-out in the push system followed by ciprofloxacin and while diclofenac injection had the highest percentage stockout in the pull system followed by ferrous sulphate tablets. Since ACT Artemether/ lumefantrine (20/120 mg) tablets are used in the treatment of malaria, the stock-outs of this drug could have had a severe impact on the health of the population within the district.…”
Section: Discussioncontrasting
confidence: 87%
“…The average availability of key medicines in the public health facilities was lower than that observed in a study conducted in Malaysia, or in the study conducted in another part of Uganda [8,9]. The average stock-out duration was also notably higher as compared to that of the studies above.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Another study done in Uganda on medicine management and procurement practices revealed that there were frequent medicine stock outs and large quantities of expired medicine in the health units due to deficiencies in selection, quantification, procurement and storage of medicines [12].…”
Section: Introductionmentioning
confidence: 99%
“…fasilitas, perlengkapan, biaya/harga, administrasi dan sistem informasi.Ketersediaan obat dalam jumlah dan jenis yang tepat bukan hanya akan meningkatkan akses terhadap obat tetapi juga akan mempengaruhi persepsi masyarakat tentang mutu pelayanan kesehatan yang diterimanya 2 . Adanya sistem suplaidengan penyerahan obat berdasarkan kebutuhan fasilitas kesehatan akan meningkatkan ketersediaan obat di puskesmas, yang harus didukung oleh sumber daya manusia yang terlatih untuk quantifikasi obat dalam melakukan permintaan obat 19 . Sistem distribusi yang efektif terutama penentuan jadwal distribusi yang konsisten dari pusat penyimpanan obat ke puskesmas dapat mengurangi keterlambatan pengiriman obat ke puskesmas.…”
unclassified